Pricing Growth-Indexed Bonds - Mauro, Paolo (International Monetary Fund, 2005)
Growth-indexed bonds have been suggested as a way of reducing the procyclicality of emerging-market countries'' fiscal policies and the likelihood of costly debt crises. Investor attitude surveys suggest that pricing difficulties are seen as a considerable obstacle. In an effort to reduce such concerns, this article presents a simple way of pricing growth-indexed bonds. As a pleasant by-product, the analysis tracks the quantitative implications of an increase in the share of growth-indexed bonds in total debt, measuring the ensuing decline in the probability of default and the reduction in the spreads at which standard bonds can be issued